Sponge microbiota are a reservoir of functional antibiotic resistance genes - Dennis Versluis; Mari Rodriguez de Evgrafov; Morten O.A. Sommer; Detmer Sipkema; Hauke Smidt; Mark W.J. van Passel (Frontiers in Microbiology, 2016)
Wide application of antibiotics has contributed to the evolution of multi-drug resistant human pathogens, resulting in poorer treatment outcomes for infections. In the marine environment, seawater samples have been investigated as a resistance reservoir; however, no studies have methodically examined sponges as a reservoir of antibiotic resistance. Sponges could be important in this respect because they often contain diverse microbial communities that have the capacity to produce bioactive metabolites. Here, we applied functional metagenomics to study the presence and diversity of functional resistance genes in the sponges Aplysina aerophoba, Petrosia ficiformis and Corticium candelabrum. We obtained 37 insert sequences facilitating resistance to D-cycloserine (n=6), gentamicin (n=1), amikacin (n=7), trimethoprim (n=17), chloramphenicol (n=1), rifampicin (n=2) and ampicillin (n=3). Fifteen of 37 inserts harboured resistance genes that shared <90% amino acid identity with known gene products, whereas on 13 inserts no resistance gene could be identified with high confidence, in which case we predicted resistance to be mainly mediated by antibiotic efflux. One marine-specific ampicillin-resistance-conferring β-lactamase was identified in the genus Pseudovibrio with 41% global amino acid identity to the closest β-lactamase with demonstrated functionality, and subsequently classified into a new family termed PSV. Taken together, our results show that sponge microbiota host diverse and novel resistance genes that may be harnessed by phylogenetically distinct bacteria.